Stability of Socio-economic Gaps in Mathematics and Science Achievement Among Canadian Schools - Ma, Xin (Canadian Journal of Education/Revue canadienne de l'éducation, 2001)
Using Canadian data from the Third International Mathematics and Science Study, I have examined the stability of within-school socio-economic gaps in mathematics and science achievement. Student characteristics had significant effects on student achievement. School characteristics were at most marginally related to school average achievement and had no effect on within-school socio-economic gaps. Within-school socio-economic gaps were highly correlated between mathematics and science, and this correlation was not affected by student and school characteristics. School average achievement was not correlated with within-school socio-economic gaps, and this relationship was not affected by student and school characteristics. L’auteur analyse la stabilité des écarts socio-économiques à l’intérieur des écoles pour ce qui est des résultats en mathématiques et en sciences. Les résultats montrent, entre autres, que les caractéristiques des élèves affectent grandement leur rendement scolaire et qu’il existe une forte corrélation entre les écarts socio-économiques à l’intérieur de l’école et le rendement scolaire en mathématiques et en sciences, cette corrélation n’étant pas affectée par les caractéristiques des élèves et des écoles. De plus, il n’y a pas de corrélation entre le rendement moyen de l’établissement et les écarts socio-économiques à l’intérieur de l’établissement.